(untitled) (Dibyajyoti Journal, 2025)
This study examines four factors influencing graduate employability: University Curricula, Teamwork and Problem-Solving Skills, Practical Training, and Personality Traits. A quantitative, descriptive–correlational design was used, with data collected from 384 bachelor’s and master’s students from diverse academic backgrounds. Findings show that all four variables are positively related to employability, but their influence differs. Teamwork and Problem-Solving Skills (β = 0.401) and Practical Training (β = 0.276) are the strongest predictors, followed by University Curricula (β = 0.193). Personality Traits were significant in correlation but not in regression, indicating a weaker predictive role when stronger variables are considered together. The model explained 47% of the variance in employability, with all constructs showing high reliability (Cronbach’s Alpha > 0.70). In conclusion, bridging Nepal’s skills gap requires a holistic approach combining academic reform, practical training, and soft skills development to produce adaptable and competitive graduates.